Rethinking Collaborative Governance in Marine Conservation: Evidence of State Dominance in Randayan Island and Its Surrounding Waters in West Kalimantan - Roma Tressa; Yulius Yohanes (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Randayan Island and its surrounding waters become a tourist destination and conservation area and raising concerns about the damage of the marine ecosystem, especially the local tourism and the local communities has a limited access to information and resources. The purpose of this study is to analyze collaborative governance by focusing on the distribution of power and stakeholder participation in marine conservation governance. A qualitative approach was used, using in-depth interviews, observation, and document analysis with government agencies, Community Monitoring Groups (Pokmaswas), NGOs, and academics. The analysis used the Ansell and Gash framework, focusing on the collaborative process. The study found that local communities and NGOs has a limited participation in decision making. The results showed that the collaboration formed was state-dominant collaborative governance due to limited local resources and the implementation of top-down policies. This study highlights that the power relations and actor capacity must be added to the collaborative governance framework. Strengthening local capacity, increasing access to information, and expanding inclusive decision-making mechanisms are needed to improve the sustainability of marine conservation governance.